KORELASI LINGKUNGAN DAN MAKANAN DARI LUAR RUMAH SAKIT DENGAN SISA MAKANAN DI RSU AGHISNA MEDIKA KROYA - Trisnawati, Yuli; Anasari, Tri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
One of the health service initiatives in hospitals is providing food as a means of delivering important nutrients to support the recovery process from illness. Minimum standards for hospital services include timely delivery of food to patients (100%), leftover food not consumed by patients (≤ 20%), and the level of accuracy in administering prescribed food (100%). The basic factor that contributes to malnutrition in hospital patients is the patient's failure to consume all the food they are given. Plate waste is a term used to describe leftover food that is wasted because it is not consumed or not finished by the patient after being served. The objective of this study is to investigate the correlation between the hospital setting and externally brought food in relation to food wastage. This research applies a descriptive analytical research design, specifically using cross sectional techniques. The sample size for this study included 67 people. The sampling strategy applied the accidental sampling method. In this research, the chi-square method is employed for analyzing data. The results of the study reveal that there is no statistically significant correlation between the hospital environment and food wastage, as indicated by a ρ-value of 0.258. However, a noteworthy correlation is observed (ρ value 0.007) between food brought from outside the hospital and the quantity of generated food waste.Keywords: hospital environment, food from outside the hospital, food waste.